Bulbostylis albidostricta (Abildgaardieae, Cyperaceae): a new sedge species from Angola - Veltjen, Emily; Browning, Jane; Goetghebeur, Paul; Larridon, Isabel (Phytotaxa, 2015)
Bulbostylis albidostricta Veltjen & Goetgh. is presented as new species of Bulbostylis (Cyperaceae) from Angola. It is a small, elegant sedge species characterised by a slender creeping rhizome, a single terminal spikelet, glumes with a translucent margin and white velate nutlets. The species is described and illustrated, and differences with the closest resembling species are discussed.